2006
DOI: 10.1021/jp062493l
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Ions in Hydrophilic Layer of Polyoxyethylated Nonionic Micelle. Cooperative Approach by Electrophoresis and Ion-Transfer Voltammetry

Abstract: Electrophoretic measurements of micellar mobility have revealed that polyoxyethylated nonionic surfactant micelles have negative zeta potential in various electrolytes, indicating that the partition of anions into the micelle dominates the entire electrolyte partition and the induced surface potential of the micelle. Although an excess of a negative charge is thus revealed in the micelle, it is uncertain whether anions are preferably solvated in the micelles or cations are expelled from the micelles. To determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…It has been confirmed that negative potential is induced on the nonionic micelle of polyoxyethylene (POE) alkyl ether as summarized in Table 3. 47 Again, the same trends predicted by the Hofmeister series, ClO4 -> I -> Br -> Cl -, are seen. Although we can estimate the number of charge excess in a micelle, negative zeta potential does not reveal whether the charge excess is caused by the preferable partition of anions or by the exclusion cations from the micelle.…”
Section: -45supporting
confidence: 64%
See 2 more Smart Citations
“…It has been confirmed that negative potential is induced on the nonionic micelle of polyoxyethylene (POE) alkyl ether as summarized in Table 3. 47 Again, the same trends predicted by the Hofmeister series, ClO4 -> I -> Br -> Cl -, are seen. Although we can estimate the number of charge excess in a micelle, negative zeta potential does not reveal whether the charge excess is caused by the preferable partition of anions or by the exclusion cations from the micelle.…”
Section: -45supporting
confidence: 64%
“…[46][47][48][49] The zeta potential of a micelle is one of the most useful physicochemical properties of a micelle. Although there is a debate on whether the shear plane corresponds to the real surface or not, the rigorous definition of the micellar surface is of no physical significance because micelles are dynamic systems that are subject to continuous thermal perturbation.…”
Section: -45mentioning
confidence: 99%
See 1 more Smart Citation
“…Moore et al also indicated by fluorophotometry that the binding constants of an anionic dye to nonionic surfactant micelles 9 were larger than that of cationic crystal violet. 8 Okada et al have indicated the selective partition of anions to nonionic polyoxylated surfactant micelle 29 and to zwitterionic surfactant micelle 30,31 through the negative ζ potential of the micelle. In this study, the weak binding affinity of nonionic Brij 58 micelle toward cationic N-alkylpyridinium ions has also been investigated with the analysis through the electrophoretic mobility.…”
mentioning
confidence: 99%
“…[ 1 ] The authors have devised a cooperative approach of mobility measurements and ion-transfer voltammetry to determine the solvation energies of single ions, and have elucidated what causes the negative zeta potential of polyoxyethylated nonionic micelles. [2] In this study, we found that the standard ion-transfer potential of ClO4-, tetramethylammonium (Me4N+), or Et4N+ was insensitive to the concentration of a hydrophilic polymer. This strongly suggests that these ions can be used for the reference in the discussion of the solvation of single ions in such media.…”
Section: Introductionmentioning
confidence: 84%